2017
DOI: 10.1111/sdi.12579
|View full text |Cite
|
Sign up to set email alerts
|

“Biocompatible” Neutral pH Low‐GDP Peritoneal Dialysis Solutions: Much Ado About Nothing?

Abstract: Adverse outcomes in peritoneal dialysis (PD), including PD related infections, the loss of residual kidney function (RKF), and longitudinal, deleterious changes in peritoneal membrane function continue to limit the long-term success of PD therapy. The observation that these deleterious changes occur upon exposure to conventional glucose-based PD solutions fuels the search for a more biocompatible PD solution. The development of a novel PD solution with a neutral pH, and lower in glucose degradation products (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 92 publications
(113 reference statements)
0
6
0
Order By: Relevance
“…Actually, a more evident increase in micro-vascular density correlating with an increase in small solute transport was seen with low GDP, neutral pH PD solutions when compared to conventional PD solutions. Though conclusions need to be drawn with caution, it has to be noted that clinical trials of low GDP, neutral pH PD solutions have failed to demonstrate a significant benefit with regards to peritoneal membrane function and UF capacity, suggesting that the presence of glucose as the main osmotic agent in PD therapy is the real culprit of the morphological changes observed in both low GDP, neutral pH and high GDP, acidic pH PD solutions [19,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Actually, a more evident increase in micro-vascular density correlating with an increase in small solute transport was seen with low GDP, neutral pH PD solutions when compared to conventional PD solutions. Though conclusions need to be drawn with caution, it has to be noted that clinical trials of low GDP, neutral pH PD solutions have failed to demonstrate a significant benefit with regards to peritoneal membrane function and UF capacity, suggesting that the presence of glucose as the main osmotic agent in PD therapy is the real culprit of the morphological changes observed in both low GDP, neutral pH and high GDP, acidic pH PD solutions [19,65,66].…”
Section: Discussionmentioning
confidence: 99%
“…Peritoneal dialysis (PD) provides life-saving kidney replacement therapy for patients with kidney failure. However, PD is associated with various complications, including local and systemic effects of glucose degradation products (GDPs) [ 1 ]. Studies have shown that exposure to GDPs is associated with mesothelial denudation, fibroblast cytotoxicity and induction of profibrotic cytokine and vascular endothelial growth factor (VEGF) synthesis [ 2–7 ].…”
Section: Introductionmentioning
confidence: 99%
“…15 This limitation is also true in the field of PD, where important questions ranging from the choice of solutions to the treatment of peritonitis or long-term membrane dysfunction remain debated. 1,[16][17][18] Yet, guidelines and recommendations may contribute to quality improvement provided they are implemented, used to develop policies and evaluated in terms of impact on clinical practice. 19 In such context, actualized recommendations for evaluating peritoneal transport have the potential to significantly impact on the field.…”
mentioning
confidence: 99%